Etiological factors and patterns of maxillofacial trauma among school-going children: A cross-sectional study at Khyber College of Dentistry, Peshawar - Awan, Usman Ayub; Ullah, Haseeb; Sanan, Adil; Manzoor, Qintar; Ilyas, Ayesha; Kamran, Shehrish; Kamran, Shehrish; Siddique, Zeeshan; Irfani, Musa Ali (BioScientific Review, 2023)
Maxillofacial trauma, such as superficial cuts and bruises, lacerations, and facial bone fractures, is a common health concern in youngsters. In this cross-sectional study, we sought to determine the prevalence and pattern of maxillofacial trauma in school-aged children (5 to 16 years) with a history of trauma. The study was conducted at the oral and maxillofacial surgery department, Khyber College of Dentistry, Peshawar. We excluded firearm injuries and maxillofacial trauma older than 15 days, whether treated or untreated, from the study. We enrolled 153 schoolchildren of both genders consecutively using non-probability sampling. To determine the etiology and nature of the trauma, we did radiographic confirmation utilizing many imaging modalities and comprehensive clinical assessments of the craniofacial region. The data was analyzed using SPSS version 22.0. The results of our study indicate that falls are the leading cause of maxillofacial injuries among school-aged children. A total of 52 (16.3%) of the patients had maxillary fractures, 30 (19.6%) had mandibular fractures, 30 (19.6%) had zygomatic-maxillary complex fractures, 23 (15%) had dentoalveolar injuries, and 45 (29.4%) had soft tissue injuries. In our study, soft tissue injuries were most prevalent among school-aged children, followed by mandibular, zygomatic-maxillary complex, and maxillary fractures. To investigate the pattern and etiology of maxillofacial injuries, we stratified the data by age, gender, and kind of school. Our findings may aid in developing effective strategies for preventing and managing maxillofacial trauma in school-aged children. These findings emphasize the necessity for focused interventions to reduce the frequency of maxillofacial trauma among school-aged children.